PENGEMBANGAN SUMBER DAYA GURU UNTUK MENINGKATKAN PENDIDIKAN RAMAH ANAK (STUDI MULTI KASUS MTsN 5 MALANG DAN SMPN 4 KEPANJEN) - Edwar, Pradine; Mulyadi; Esa Nur Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Human resource development, especially for teachers, plays an important role in creating child-friendly education. Teacher resource development as a strategy to improve child-friendly education. With a focus on improving teachers' teaching quality and interpersonal skills, this study highlights the importance of training and continuous professional development. The methods used include qualitative analysis of teachers' experiences and direct observation in a child-friendly classroom context. Effective teacher resource development contributes to a more positive and inclusive learning environment for children. This article explores a range of strategies and practices that can be implemented to improve teachers' competencies in supporting safe and inclusive learning environments. With an approach that focuses on improving pedagogical skills and understanding of children's needs, professional development for teachers is expected to have a positive impact on the quality of education. The results of the two institutions show that the development process in schools is an introduction to child-friendly education, including parents to take part in running the program. In addition, the supporting factors and obstacles that exist in the institution are the understanding of educators and education personnel in implementing child-friendly programs, adequate facilities that must be adapted to the needs of children.